Flame retardant cellulosic fabrics via layer-by-layer self-assembly double coating with egg white protein and phytic acid. (10th January 2020) - Liu, Xiaohui; Zhang, Qiuyan; Peng, Bo; Ren, Yuanlin; Cheng, Bowen; Ding, Chen; Su, Xiaowei; He, Ju; Lin, Shenggen
Abstract: In this work, facile and inexpensive egg white protein with numerous amino acids, calcium, ferric, sulfur, and phosphorus was firstly explored to flame retard cellulosic fabrics. This was achieved by generated phosphorus-nitrogen flame retardant system formed by intense electrostatic attraction of egg white protein and phytic acid (PA) with special hexaphosphate-substituted cyclic structure. As expected, the cotton fabrics treated by protein and PA in sequence exhibit high residue and time to ignition as well as low values for peak of heat release rate and total heat release after burning than those of control fabrics evaluated by thermogravimetric and cone calorimeter analyses, which is comparable or prior to other biomaterials. The results suggest that the treated fabrics displayed excellent flame retardancy properties, which is ascribed to synergistic effect of phosphorus and nitrogen granted by the double-coating system of PA and egg white protein. Highlights: Egg white protein and phytic acid were employed to treat cellulosic fabrics. Treated fabrics show high residue and time to ignition, and low total heat release. High flame retardancy efficiency owing to synergism of P and N elements was proved.